Transnational Corporations in the World Economy: Formation, Development and Present Position - Małgorzata Jaworek; Marcin Kuzel (Copernican Journal of Finance & Accounting, 2015)
The following article attempts to answer the question about the role transnational corporations (TNCs) play in the modern world. The issues discussed in this article have been presented in two main parts. The first part focuses on the world’s largest TNCs according to the following criteria: the value of the revenues, market capitalization and foreign assets. The discussion in the second part focuses on defining the role that transnational corporations play in the world economy. A number of different characteristics reflecting the economic potential of TNCs have been used in this article such as: asset value, employment rate, sales volume and research and development potential, which are linked to selected parameters describing the volume of international production. The analysis of TNC development and their present position has been presented from a historical perspective, which made it possible to identify the conditions of as well as the major changes in the process of enterprise internationalisation. The following article highlights the dynamic development of corporations in developing countries and the ever more common phenomenon of state-owned enterprises or enterprises with a state’s capital playing a role on the international stage.